THE EXPERIENCE OF OWN CHOICE AND PERSONAL QUALITIES OF STUDENT SELF-GOVERN- MENT LEADERS - Яновська, Світлана Германівна; Туренко, Римма Леонардівна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2018)
The article presents the results of the study on determining the characteristics of the relationship between theexperience of own choice and the personal qualities of students-leaders in student self-government. The study was conducted in two stages: the fist one - in 1-2 weeks before the elections to the student councils of the faculties, the second - in 2 weeks after the elections. For each stage we have developed questionnaires. It was determined how students relate to student self-government, how much they are aware of their work. Student leaders who were convinced that their decision to participate in the Student Council could affect the quality of life and university students’ training, were more confient about the high quality of work and the importance of student self-government. The choice of those who are better informed about student self-government and determine their subjective importance is more moderate and stable, and is characterized by rationality, independence, responsibility, positive attitude to it, and also accompanied by a sense of its signifiance. It has been established that there is a correlation between the results of the choice and thebehavior associated with it, with the attitude of the individual to the choice: the students who took part in the elections to the student council were more satisfid with the outcome of the election, compared with those who did not participate.The relationship between the personality traits of the student and student leader and the subjective quality of choice was determined: the thoughtfulness of the choice positively correlates with the factor «Power» and the organizational skills of the leaders and with the factor «Activity» student’s self-assessment; the positive attitude to the process of selection is related to the «Power» factor and the communicative skills of the leaders and the Locus of Control I and Life; Independence of choice is related to the satisfaction of all the students studied with the results of the election.